TINJAUAN YURIDIS TINDAK PIDANA ABORSI YANG DILAKUKAN ANAK DIBAWAH UMUR - Nuralisyah Nuralisyah (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTAbortion is a threat or release of the product of conception before the fetus can live outside the womb and as a limitation is used for pregnancies of less than 20 weeks or fetal weight less than 500 grams. The development of the era of globalization has made the moral values that exist in society less and less free so that it violates the boundaries of moral and religious values. Currently, the crime of Abortion is evidence of the increasing importance of free sex among young women, especially underage children in the jurisdiction of the city resort police. Samarinda. Regarding abortion, the problem in this study is how the methods of law enforcement and efforts to overcome and reduce abortion crimes committed by minors by the Samarinda City Resort Police. This research method uses empirical legal research, namely research with field data as the main data source such as interviews. The conclusion obtained is that the police carry out law enforcement methods on abortion carried out by minors by using applicable rules such as Law No. 11 of 2012 concerning the Criminal Justice System for Children and Law Number 36 of 2009 concerning Health. To overcome or reduce the crime of Abortion by means of Preventive Efforts and Repressive Efforts.